A convenient one-pot synthesis of ketone cyanohydrin esters in aqueous media - Sirawit Wet-Osot (2018)
© 2015 Elsevier Ltd. All rights reserved. A convenient one-pot, two-step procedure for the synthesis of ketone cyanohydrin esters in aqueous media is reported using N-acylbenzotriazoles as the acylating agents. In saturated aqueous sodium bicarbonate containing a catalytic amount of tetrabutylammonium bromide, the reaction of ketones with potassium cyanide and N-acylbenzotriazoles proceeded readily at room temperature to provide the corresponding O-acyl cyanohydrin derivatives in good to excellent yields.